Pemberdayaan Masyarakat dalam Pemanfaatan Pangan Lokal Sebagai Makanan Selingan bagi Keluarga Penderita Diabetes Melitus Tipe 2 - Ismawanti, Zuhria; Ambarwati, Ria; Permatasari, Arvina Dian Wahyu; Firnanda, Tiara; Nafi'ah, Ulin; Zhurifa, Zahwa Mahda; Muhlishoh, Arwin; Permatasari, Oktavina (Abdi Geomedisains, 2024)
Diabetes mellitus (DM) is a collection of symptoms that arise in a person due to the body experiencing problems in controlling blood sugar levels. The lower the knowledge, the higher the blood sugar levels. The low knowledge of respondents about DM disease makes respondents unable to control blood sugar levels. This community service aimed to enhance public knowledge about DM prevention through education on local food consumption and healthy behaviors. The activity was carried out in Kedungmundu, Semarang City, in August 2024, with the participation of 39 people. The education was delivered through lectures, discussions, and a booklet, containing information about DM, recommended diets, and the use of local food. The results of the activity showed a significant improvement in community knowledge about DM prevention, with post-test scores higher than pre-test scores. This increase indicates that education through lectures and booklets was effective in disseminating health information. With better knowledge, the community is expected to adopt healthier behaviors that can reduce the prevalence of DM, particularly through the use of lokal food. This activity made an important contribution to promotive and preventive efforts to control DM within the community. Future research is recommended to explore the impact of increased knowledge on changes in community attitudes and behaviors in DM prevention.